MIXER DESIGN EQUIPPED WITH HEATING CONTROL ELEMENTS FOR MANUFACTURING COMPOSITE MATERIALS - Rifki Hidayat; Erwhin Irawan; Erwan Eko Prasetiyo; Fery Setiawan (Indonesian Society of Applied Science, 2022)
Composite is a composite material consisting of two or more materials with different mechanical properties. Composite materials are mixed to obtain new materials that have better micro-mechanical properties. To facilitate the mixing of composite materials and obtain materials that have good quality, in this study, a mixer machine design with heating elements was carried out so that the temperature could be adjusted as needed. Experiments from the results of a mixer machine with a heating element that have been made are comparing the mixing of resin and iron sand using a mixer machine without a heating element and using a heating element. The result of mixing composite materials using a mixer machine without heating elements is that the composite material is homogeneously mixed but when viewed from the micro-photos there are still many white spots so that the quality of the composite material is still not good. then the composite material is mixed and mixed using a mixer machine with a heating element, the composite material is homogeneously mixed and after seeing from the micro-photos there are a few wite spots on the composite.